x - 5,5 = 4,5 + 3,2
x - 5,5 = 7,7
x = 7,7 + 5,5
x = 13,2
Vậy: x = 13,2
Nhớ k cho mình nhé! Thank you!!!
(x-5,5) =4,5+3,2
x-5,5=7,7
x=7,7-5,5
x=2,2
tk mk nhé
(x - 5,5) - 3,2 = 4,5
x - 5,5 = 4,5 + 3,2
x - 5, 5 = 7,7
x = 7,7 - 5, 5
x = 2,2
( x - 5,5 ) - 3,2 = 4,5
x - 5,5 = 4,5 + 3,2
x - 5,5 = 7,7
x = 7,7 + 5,5
\(\Rightarrow\)x = 13,2
Vậy x = 13,2
( x - 5,5 ) - 3,2 = 4,5
x - 5,5 = 4,5 + 3,2
x - 5,5 = 7,7
x = 7,7 + 5,5
⇒x = 13,2
P/s tham khảo nha
2 , thank tất cả các bạn đã giúp tớ trả lời câu hỏi mình làm bn nha